Meta-Analysis Assessing the Effects of Virtual Reality Training on Student Learning and Skills Development - Angel-Urdinola, Diego F. (World Bank, Washington, DC, 2021)
Training using virtual reality has been applied in many fields of education, but primarily in the fields of health and safety, engineering and technical education, and general education. Numerous studies assessing the use of immersive training in education have yielded promising results in educational outcomes, but there is not yet in the literature a systematic analysis of the effects of virtual reality training on student learning. This paper presents a meta-analysis of the results of available studies that assess virtual reality training’s impact on student learning and skills development, and which rely on robust evaluation methods. The study’s primary purpose is to identify the extent to which immersive training can successfully develop students’ skills across different fields of education and the size of the effects encountered. The analysis presented here relies on 31 primary studies and more than 90 experiments. The results indicate that, on average, virtual reality training is more effective than traditional training in developing technical, practical, and socio-emotional skills. The results are particularly promising in fields related to health and safety, engineering, and technical education. The results also indicate that students who are exposed to virtual reality training are more efficient in using inputs and time and/or avoiding performance errors than students receiving traditional training.